Exosome miR-155 Derived from Gastric Carcinoma Promotes Angiogenesis by Targeting the c-MYB/VEGF Axis of Endothelial Cells - Deng, Ting (Mol Ther Nucleic Acids, 2020)
Exosomes, membranous nanovesicles, naturally carry proteins, mRNAs, and microRNAs (miRNAs) and play important roles in tumor pathogenesis. Here we showed that gastric cancer (GC) cell-derived exosomes can function as vehicles to deliver miR-155 to promote angiogenesis in GC. In this study, we first detected that the expression of miR-155 and c-MYB was negatively correlated in GC and that c-MYB was a direct target of miR-155. We next characterized the promotional effect of exosome-delivered miR-155 on angiogenesis and tumor growth in GC. We found that miR-155 could inhibit c-MYB but increase vascular endothelial growth factor (VEGF) expression and promote growth, metastasis, and tube formation of vascular cells, causing the occurrence and development of tumors. We also used a tumor implantation mouse model to show that exosomes containing miR-155 significantly augment the growth rate of the vasculature and tumors in vivo. Our results illustrate the potential mechanism between miR-155 and angiogenesis in GC. These findings contribute to our understanding of the function of miR-155 and exosomes for GC therapy.